ANALYSIS PREDICTION BANKRUPTCY BUSINESS BY USING THE METHOD ALTMAN Z-SCORE AND METHODS SPRINGATE (STUDY IN PT HOLCIM INDONESIA TBK.) - Mulyadi, Dedi; Sihabudin; Gusni (International Journal of Psychosocial Rehabilitation, 2020)
Bankruptcy is a condition where a company has financial difficulties that make business failures and harm many parties. Bankruptcy itself becomes a threat to companies that do not realize early on the existence of business bankruptcy. Therefore, it is necessary to predict bankruptcy early on. There are several ways to predict bankruptcy by analyzing financial ratios with Altman Z-Score and Springate Methods. This study aims to determine the company’s financial performance by using the ratio of financial analysis and prediction analysis of bankruptcy method Altman Z-Score and Springate Method. This study uses secondary data obtained from the financial statements of PT Holcim Indonesia Tbk period 2010 to 2014. To know the financial performance of the company there are 5 ratios used consisting of liquidity, solvency, activity, profitability and market ratios. Then to predict bankruptcy by the Altman Z-score method and the Springate method. Altman Z-Score method consists of Working Capital to Total Assets, Retained Earning to Total Assets, Earning Before Interest and Tax to Total Assets, Market Value of Equity to Book Value of Debt, Sales to Total Aseets. Springate method consist of 4 ratio namely Working Capital to Total Assets, Earning Before Interest and Tax to Total Assets, Earning Before Tax to Current Liabilities, Sales to Total Assets. The results showed the company’s financial performance with ratio analysis from the period 2010 to 2014 showed the company in good condition because there is no negative result even though every year the results fluctuate. The results of bankruptcy analysis by the method of Altman Z-Score in the period 2010 to 2013 are categorized not bankrupt and in 2014 categorized the company is in the area of gray or hesitant. The results of bankruptcy analysis by Springate method in the period 2010 to 2012 companies are categorized not bankrupt and in the period 2013 to 2014 companies are categorized bankrupt.